The Correlation of Students’ Anxiety and Self-Confidence toward Their Speaking Ability - Helda Pebriyana (Universitas Pendidikan Mandalika, 2018)
This study was aims to find out whether or not any correlation between students’ anxiety and self-confidence toward speaking ability. This study used quantitative method. The study was conducted at the second grade students of MTs NW Tanak Maik in academic year 2017. The total of population was 28 students in one class. The total of sample was 28 students. The technique of data analysis was Pearson Product Moment formula and Multiple Linear Regressions to know the correlation between students’ anxiety, self-confidence and speaking ability. The result of computation between speaking and anxiety was 0,683, speaking ability and self-confidence was 0,557, anxiety and self-confidence was 0,437. The result of anxiety, self-confidence and speaking ability was 0,549. It means that those variables were there a correlation, because t-test was higher than t-table. The alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. The result also showed that the value of significant correlation was very high.